Kajian Pemasangan Lampu Penerangan Jalan Umum dengan Panel Surya Sebagai Sumber Energi Alternatif di Politeknik Negeri Balikpapan - Subur Mulyanto; Yudi Kurniawan; Arwin; Herdian Dwimas; Nurul Huda (Universitas Islam Raden Rahmat, Malang, 2024)
Balikpapan State Polytechnic seeks to support the reduction of greenhouse gas emissions through the development of renewable energy sources. This is realized in the installation of solar powered Public Street Lighting (PJU) lamps installed at 11 locations. From this research, 11 locations for solar street street installations have been determined on a 250 meter long road using 12V24W DC lights. Energy storage obtained from solar cells using a 50Ah capacity battery to capture solar energy using 100 wattpeak solar panels. From this research, it was found that the distance between poles was 8.6 meters, and the distance between poles from the road shoulder was 2.036 meters.